2023
DOI: 10.1111/ijal.12501
|View full text |Cite
|
Sign up to set email alerts
|

“Behind the Screen, I Still Care about my Students!”: Exploring the emotional labour of English language teachers in online teaching during the COVID‐19 Pandemic

Honggang Liu,
Hanxi Li,
Fan Fang

Abstract: Foreign language teachers’ management of their emotional expression has a significant impact on their classroom teaching and professional development. As the demand for online education continues to grow, researchers are increasingly paying attention to the emotional situations of teachers in online teaching. However, there has been minimal research on secondary school English as a foreign language (EFL) teachers, particularly during the COVID‐19 pandemic when online teaching became the norm. By combining two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is constructed through their interactions with students, colleagues, administrators, and other parties in their respective pedagogical, institutional, and sociohistorical contexts (Ding et al, 2022). Previous studies have sought to investigate teacher emotion in the context of both offline teaching (e.g., Gkonou and Miller, 2021;Nazari et al, 2023) and online teaching (e.g., Gu et al, 2022;Liu et al, 2022Liu et al, , 2023Wang and Song, 2022). Researchers found that although teachers in the offline teaching context shared some unpleasant emotional experiences (such as frustrations and anxiety), their dominant emotions were more positive than negative (Cross and Hong, 2012;Richards, 2022;Goetze, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It is constructed through their interactions with students, colleagues, administrators, and other parties in their respective pedagogical, institutional, and sociohistorical contexts (Ding et al, 2022). Previous studies have sought to investigate teacher emotion in the context of both offline teaching (e.g., Gkonou and Miller, 2021;Nazari et al, 2023) and online teaching (e.g., Gu et al, 2022;Liu et al, 2022Liu et al, , 2023Wang and Song, 2022). Researchers found that although teachers in the offline teaching context shared some unpleasant emotional experiences (such as frustrations and anxiety), their dominant emotions were more positive than negative (Cross and Hong, 2012;Richards, 2022;Goetze, 2023).…”
Section: Introductionmentioning
confidence: 99%